Otitis media guidelines for Australian Aboriginal and Torres Strait Islander children: summary of recommendations. Issue 5 (28th February 2021) - Leach, Amanda J; Morris, Peter S; Coates, Harvey LC; Nelson, Sandra; O'Leary, Stephen J; Richmond, Peter C; Gunasekera, Hasantha; Harkus, Samantha; Kong, Kelvin; Brennan‐Jones, Christopher G; Brophy‐Williams, Sam; Currie, Kathy; et al.
Abstract: Introduction: The 2001 Recommendations for clinical care guidelines on the management of otitis media in Aboriginal and Torres Islander populations were revised in 2010. This 2020 update by the Centre of Research Excellence in Ear and Hearing Health of Aboriginal and Torres Strait Islander Children used for the first time the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Main recommendations: We performed systematic reviews of evidence across prevention, diagnosis, prognosis and management. We report ten algorithms to guide diagnosis and clinical management of all forms of otitis media. The guidelines include 14 prevention and 37 treatment strategies addressing 191 questions. Changes in management as a result of the guidelines: A GRADE approach is used. Targeted recommendations for both high and low risk children. New tympanostomy tube otorrhoea section. New Priority 5 for health services: annual and catch‐up ear health checks for at‐risk children. Antibiotics are strongly recommended for persistent otitis media with effusion in high risk children. Azithromycin is strongly recommended for acute otitis media where adherence is difficult or there is no access to refrigeration. Concurrent audiology and surgical referrals are recommended where delays are likely. Surgical referral is recommended for chronic suppurative otitis media at the time of diagnosis. The use of autoinflation devices is recommended for some children with persistent otitis media with effusion. Definitions for mild (21–30 dB) and moderate (> 30 dB) hearing impairment have been updated. New "OMapp" enables free fast access to the guidelines, plus images, animations, and multiple Aboriginal and Torres Strait Islander language audio translations to aid communication with families.